Thermothelomyces thermophilus exo- and endo-glucanases as tools for pathogenic E. coli biofilm degradation - Samaniego, Lorgio Victor Bautista; Scandelau, Samuel Luis; Silva, Caroline Rosa; Pratavieira, Sebastião; de Oliveira Arnoldi Pellegrini, Vanessa; Dabul, Andrei Nicoli Gebieluca; Esmerino, Luís Antônio; de Oliveira Neto, Mario [UNESP]; Hernandes, Rodrigo Tavanelli [UNESP]; Segato, Fernando; Pileggi, Marcos; Polikarpov, Igor (Springer Nature, 2024)
The escalating prevalence of drug-resistant pathogens not only jeopardizes the effectiveness of existing treatments but also increases the complexity and severity of infectious diseases. Escherichia coli is one the most common pathogens across all healthcare-associated infections. Enzymatic treatment of bacterial biofilms, targeting extracellular polymeric substances (EPS), can be used for EPS degradation and consequent increase in susceptibility of pathogenic bacteria to antibiotics. Here, we characterized three recombinant cellulases from Thermothelomyces thermophilus: a cellobiohydrolase I (TthCel7A), an endoglucanase (TthCel7B), and a cellobiohydrolase II (TthCel6A) as tools for hydrolysis of E. coli and Gluconacetobacter hansenii biofilms. Using a design mixture approach, we optimized the composition of cellulases, enhancing their synergistic activity to degrade the biofilms and significantly reducing the enzymatic dosage. In line with the crystalline and ordered structure of bacterial cellulose, the mixture of exo-glucanases (0.5 TthCel7A:0.5 TthCel6A) is effective in the hydrolysis of G. hansenii biofilm. Meanwhile, a mixture of exo- and endo-glucanases is required for the eradication of E. coli 042 and clinical E. coli biofilms with significantly different proportions of the enzymes (0.56 TthCel7B:0.44 TthCel6A and 0.6 TthCel7A:0.4 TthCel7B, respectively). X-ray diffraction pattern and crystallinity index of E. coli cellulose are comparable to those of carboxymethyl cellulose (CMC) substrate. Our results illustrate the complexity of E. coli biofilms and show that successful hydrolysis is achieved by a specific combination of cellulases, with consistent recurrence of TthCel7B endoglucanase.